ANALISIS YURIDIS TUGAS POKOK DAN FUNGSI KESYAHBANDARAN DALAM PROSES PENDAFTARAN AKTA HIPOTIK KAPAL - Nurhan Nurhan (JURNAL HUKUM DAS SOLLEN, 2017)
Shipping means to economic wheel, strengthen national unity, in establishing embodiment archipelago insight, enhance and support national defense and security which could further strengthen the relations between nations, in addition to the cruise also act as supporting, driving and driving force for economic growth in Indonesia, shipping business in carrying out those activities would require a large capital. provision of capital carried out by financial institutions, and of course accompanied by a guarantee and one of the security institutions are mortgages. The setting is KUHD ship registration law, Law No. 17 of 2008, Government Regulation No. 51 of 2002, and the Regulation of the Minister of Transportation PM Number 13 Year 2012. Imposition of a mortgage on the vessel carried by the ship mortgage deed by Acting Registrar and Registrar Baliknama ships in the boat is registered and recorded in the master list of the ship concerned